2019
DOI: 10.9734/jeai/2019/v41i630436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Variety and Seedling Number on the Growth and Yield of Boro Rice in Bangladesh

Abstract: Rice is the most important human food crop in the world. In Bangladesh rice is cultivated throughout the year as Aus, Aman and Boro. Among them boro rice is generally cultivated in November to March. More than half of the total production (55.5%) is obtained in this season. Generally, farmers use more than the recommended number of seedlings during transplanting. The number of seedlings plays a vital role in the growth, development and yield of rice. The aim of this experiment was to determine the number of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 10 publications
7
7
0
Order By: Relevance
“…First crop of CP 2 (Fig 2), Binadhan-16 attained a grain and straw yield of 4.61 t/ha and 5.24 t/ha. These results are alike with the findings of Chowhan et al (2019). Binasarisha-10, the second crop of this pattern gave less production than CP 3 .…”
Section: Productivity and Yield Of Five Patternssupporting
confidence: 89%
See 4 more Smart Citations
“…First crop of CP 2 (Fig 2), Binadhan-16 attained a grain and straw yield of 4.61 t/ha and 5.24 t/ha. These results are alike with the findings of Chowhan et al (2019). Binasarisha-10, the second crop of this pattern gave less production than CP 3 .…”
Section: Productivity and Yield Of Five Patternssupporting
confidence: 89%
“…It matured at 95 DAT. Chowhan et al (2019) found duration of Binadhan-14; 126.11 days with varietal effect.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations